Exploring How Novice Teachers in the UK Leverage Reflective Teaching to Enhance Classroom Assessment Practices - Alexander T. Whitman (Research and Advances in Education, 2024)
Reflective teaching has emerged as a critical practice for enhancing classroom assessment, particularly for novice teachers. This study explores how new educators in the UK leverage reflective practices to improve their assessment methods, ensuring they align with diverse student needs and learning objectives. Drawing on theoretical frameworks such as Schön’s Reflective Practitioner Model and Kolb’s Experiential Learning Cycle, the study highlights the practical approaches that novice teachers adopt, including reflective journaling, peer feedback, and self-assessment. Through case studies and empirical evidence, the research demonstrates the significant impact of reflective teaching on improving assessment accuracy and fostering student engagement. Despite its benefits, reflective teaching is not without challenges. The study also examines common barriers, such as time constraints and lack of guidance, and discusses support mechanisms that can facilitate effective reflective practices. This research underscores the importance of reflective teaching in promoting professional growth and enhancing educational outcomes.